HUBUNGAN PENGETAHUAN IBU DENGAN SIKAP IBU HAMIL TERHADAP SENAM HAMIL DI PUSKESMAS SRANDAKAN, BANTUL - Lutfiyati, Afi; Yati, Dwi (MEDIA ILMU KESEHATAN, 2020)
Background: Pregnancy exercise movement contains a relaxing effect that could stabilize emotionally pregnant women. In women who do pregnancy exercise, delivery is faster than pregnant women who do not do pregnancy exercises. Pregnant exercise, is very important for pregnant women, because it could reduce discomfort during pregnancy and facilitate the delivery process. Attitudes and practices were important components that pregnant women must have in carrying out pregnancy exercises. there were several factors that influence the attitude of pregnant women to pregnancy exercise including knowledge of the woman. Objectives: The aim of this study were to identify the association between knowledge with the attitude of pregnant women to pregnancy exercise. Methods: The study were used quantitative research design with a cross-sectional study approach. Samples were taken by purposive sampling technique, namely 36 pregnant women who carried out antenatal care at the Srandakan Health Center. The research instrument was a questionnaire. The results of the study were analyzed using the chi-square analysis. Results: Most mothers also had good knowledge as much as 69.4%. While the mother's attitude about pregnancy exercise mostly supports as much as 52.8%. The chi-square test results obtained p values=0,191 (> 0.05). Conclusions: There were no association between knowledge with the attitude of pregnant women to pregnancy exercise at the Srandakan Health Center.